Growth, Somatic Maturation and Their Impact on Physical Health and Sports Performance - Campa, Francesco; Greco, Gianpiero (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
A total of 11 manuscripts focused on different topics related to youth and sports practice are published in this book. Three papers focus on aspects of physical performance, five papers provide innovative findings in relation to anthropometry and body composition features, one paper examines the difficulties in running online physical education classes in the context of COVID-19, and two focus on the influence of training strategies on muscle strength and blood pressure.